حقوق الاقليات في الدساتير التركية واتجاهات تطورها المستقبلي - الله, يوسف صمد لطف (Journal of Legal and Political Studies, 2013)
The problem of minority right is not a new question in Turkish political and constitutional agenda, it was emerging since the ottoman empire at 19 century, after that this case transformed to modern Turkish republic in 1923. In all republic constitutions the constitution right of minorities not seen and not definitions in constitution. the constitution a Article see that the identity of state is turkishness an there is one formal language in turkey, there is no way to study another local language of minority in formal education. The constitutional policy of turkey amendment in 2001 and 2010 not care about minority right and there is a doubt to see any fundamental minority right in new draft constitution.
Keywords: problem of minority; constitutional agenda; Amendment; Constitution